ANALISA KESADAHAN TOTAL DAN KADAR KLORIDA AIR DI KECAMATAN TANGGULANGIN SIDOARJO - Devyana Dyah Wulandari (UNUSA Press, 2017)
Subdistrict Tanggulangin was relatively close to the source of the Lapindo mud flow, the release of mud content into the water will cause the death of aquatic organisms and lead to serious consequences for humans who depend their life on these waters. Therefore, researchers seek to determine the total water hardness and chloride content in Tanggulangin district. Water make up the population and sample, taken from 15 points in Tanggulangin, Sidoarjo. Total hardness determination was conducted using complexometric titration method, whereas chloride content wasperformed using argentometry Mohr titration method. Water sample from 3 of 10 regions in Tanggulangin is drinkable, namely the sample A (320 mg / L), sample C (170 mg / L), sample E (304 mg / L), sample F (298 mg / L), sample I (372 mg / L), samples J (340 mg / L). While the in the othersamples, the content of total hardness exceeds the maximum threshold (> 500 mg / L) which means unfit for consumption, and 5 of the 10 areas in the district is drinkable, namely the sample A (123.2 mg / L), sample C (49.7 mg / L), sample E (245.7 mg / L), sample I (182.4 mg / L), and samples J (64mg / L).